Influence of Professional Status and Conditions of Services on Teacher Productivity in Primary Schools in Zuru Emirate, Kebbi State, Nigeria - MANGA, Sani Dantani (International Journal of Scientific Research and Management (IJSRM), 2020)
This study investigated the influence of professional status and condition of service on teacher productivity in primary schools in Zuru Emirate of Kebbi State. A correlational survey design was adopted for the study. Stratified, proportionate and simple random sampling techniques were used to select 346 teachers out of 3,687. Questionnaire and Teacher Productivity Evaluation Format were used as instruments for data collection. The five-point scale instruments were validated by experts and pilot tested and had reliability indexes of 0.83 and 0.85 respectively, using Cronbach Alpha co-efficient. Findings of the study showed that the level of teacher productivity was rated low; professional status and conditions of service were both rated poor. This unfavourable situation has negatively influenced teacher productivity. It was recommended that strategies be put in place to improve teachers’ productivity in terms of quality of teaching, record keeping and other activities. The status of teaching should be upgraded and primary school teachers to be provided with better conditions of service to enhance their productivity